Teachers’ Self-Efficacy as a Mediator of Their Perception and Behavior regarding Creative Teaching for Elementary School Students - Sutjonong, Winda Ria; Salim, Rose Mini Agoes; Safitri, Shahnaz (Universitas Pendidikan Indonesia, 2022)
Creativity must be considered in teaching elementary school students to prepare them to be more innovative. It needs to be fostered from an early age because children at that age are in a critical period, so it will be easier to teach them to think creatively. The teachers have roles to carry out creative teaching to foster their students’ creativity. Creative teaching is influenced by the teachers’ perception of creativity, which depends on several factors, one of which is the teachers’ self-efficacy. This study aims to examine whether the teacher’s self-efficacy can mediate the relationship between teachers’ perceptions of creativity and their creative teaching behavior in class. Participants of this study were 38 elementary school teachers who were participants in the Creative Teaching Workshop. The measuring tools used in this study are the Creativity Fostering Teacher Index (CFTI) and Teaching for Creativity Scale (TFCS). The data obtained were analyzed quantitatively using correlation tests (Pearson’s correlation) and mediation tests with Macro PROCESS. The results found that teachers’ self-efficacy partially mediated teachers’ perceptions of creativity and creative teaching behavior, which means that the relationship between teachers’ perceptions and behaviors can be explained directly and indirectly through the teachers’ self–efficacy.